Our first experience of prepectoral reconstruction of the mammary gland using a mesh polypropylene implant - D. N. Rovenskikh; S. A. Usov; S. V. Petrosyants (Исследования и практика в медицине)
Purpose of the study. To study the results of prepectoral reconstruction of the mammary gland after subcutaneous mastectomy for cancer with additional covering of the implant with a polypropylene mesh implant. (IPPBR)Materials and methods. Case-series of 6 patients with luminal breast cancer T1–2N0M0 aged from 34 to 47 years. IPPBR was performed after subcutaneous mastectomy (nipple sparing in 2 cases). The anterior surface of implants (Polytech, Germany) was covered with Ethicon/Johnson& Johnson (USA) simple polypropylene mesh. The mesh was fixed with interrupted absorbable sutures to the big pectoral muscle.Results. There was one successfully treated minor complication: limited skin incision necrosis. No other complications or tumor recurrences were registrated during observation period. The aesthetic results (mainly shape and volume breasts symmetry, nipples symmetry after nipple- sparing operation) were estimated as good both by surgeon and all patients. Periprosthetic connective tissue growth was minimal (grade I due to Baker’s scale) in all cases.Conclusion. The first results of the use of a simple mesh polypropylene implant in cases of breast cancer after subcutaneous mastectomy for cancer for the prevention of implant migration are encouraging. The degree of development of periprosthetic scar contracture is minimal.